2012
DOI: 10.1002/acr.21741
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of magnetic resonance imaging–based knee cartilage T2 measurements and focal knee lesions with body mass index: Thirty‐six–month followup data from a longitudinal, observational multicenter study

Abstract: Objective To compare MRI-based knee cartilage T2 measurements and focal knee lesions and 36 month changes in these parameters, among knees of normal controls and knees of normal-weight, overweight, and obese subjects with risk factors for knee osteoarthritis (OA). Methods 267 subjects aged 45–55 years from the Osteoarthritis Initiative (OAI) database were analysed in this study. 231 subjects had risk factors for knee OA, but no radiographic OA (KL-score≤1) at baseline. 36 subjects were normal controls. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 46 publications
3
50
3
Order By: Relevance
“…16,17,49 Data from the OAI show that in asymptomatic adults and those with OA risk factors, obese individuals had the highest T2 values and normal-weight individuals had the lowest mean T2 values. 4 In cohorts of less than 30 individuals, people with medial knee OA who had varus alignment were found to have higher cartilage T1rho and T2 than those with valgus alignment. 20,55 Most of these studies either were in healthy cohorts or had a small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…16,17,49 Data from the OAI show that in asymptomatic adults and those with OA risk factors, obese individuals had the highest T2 values and normal-weight individuals had the lowest mean T2 values. 4 In cohorts of less than 30 individuals, people with medial knee OA who had varus alignment were found to have higher cartilage T1rho and T2 than those with valgus alignment. 20,55 Most of these studies either were in healthy cohorts or had a small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Possible explanations for this discrepancy include the differences in study designs (cohort studies vs. matched case-control study), different inclusion criteria (knees with and/or without radiographic OA 2,9,10 vs. knees with established radiographic OA [KLG 2/3]), and different definitions of progression (incidence or worsening of semi-quantitative cartilage lesion scores vs. loss in both MRI-based cartilage thickness and radiographic JSW in the medial femorotibial compartment). To avoid potential bias from disease-related covariates such as BMI 20,21 , the presence or absence of radiographic OA 14,15 , or pain 19 , a matched case-control design controlling for these factors was chosen for the current study. It is of note that a sensitivity analysis in the study by Prasad et al 10 found the association with progressor status to disappear, once knees with and without definite radiographic knee OA were analyzed separately, which accords with the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[1718] Age and BMI were included because these variables were significantly different between the groups and are known to be related to cartilage MR relaxation times. [1920] Gender was included because prevalence of knee OA is higher in women than men. The GEE model was first run with the interaction between group (Control vs. OA) and Condition (repeated measure).…”
Section: Methodsmentioning
confidence: 99%